Lying awake - Salzman, Mark (New York Vintage Books, 2000)
In a Carmelite monastery outside present-day Los Angeles, Sister John of the Cross experiences visions of such dazzling power and insight that she is considered a spiritual master. But they are accompanied by powerful headaches, and when a doctor reveals they may be dangerous, she faces a devastating choice since she fears a "cure" may end her spiritual gifts.
AC-12854D donated by Vivienne Angeles
Keywords: Epileptics -- Fiction; Visions -- Fiction